Перспективы повышения поверхностной прочности и противозадирной стойкости триботехнических композитов - Бондаренко, В.П.; Андреев, И.В.; Бондарь, В.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Fracturing behaviors of the surface stratums of materials for abrasion with weighing materials of the high module at their dray friction and perspectives directions of a heightening of their surface strength and durability to a score are observed.